Project feasibility study on CocoBlast! the nature's sports drink - Abundo, Elvy Grace; Margallo, Nestor; Sedilla, Keneth; Urrutia, Leah Marie
A study about softdrinks in the Philippines showed that future sales of soft drinks are anticipated to get a boost by the surging demand for non-carbonated drinks such as sports drinks, bottled tea drinks, and bottled fruit juices. Analysts believe that a key factor in this continued growth is the growing health awareness and healhy safety concerns among the Filipino population. In the NCB industry, sports drinks are among the products that exhibit a positive growth-sports drinks compounded annual growth rate for 2008-2009 was 13.4%. Furthermore, it is expected that sports drinks sales would continue to improve as more and more health-conscious Filipinos engage themselves in sports, exercise, and other forms of physical activities. For several years, sports drinks market in the Philippines, just like its world market counterpart, has been dominated by Gatorade which was holding a 91% market share. But despite the fact that the market is controlled by Gatorade, the positive growth in sports drinks sales still gives very attractive, lucrative prospects. That is why this study aimed to test the feasibility of introducing a new brand of sports drink in the market, a sports drink that would be locally-made, a sports drink that would be known by the name CoCoBlast. CoCoBlast was conceptualized in order to better suit the wants and needs of the growing health conscious Filipino market-a sports drink that was made healthier and possibly more appealing to the Filipino market because it would have coconut water as a major ingredient. Young coconut water or buko water has always been known to Filipinos as a very healthy fluid, primarily used as a body cleansing drink. It is a very coomon cooling and refreshing solution that Filipinos have been drinking since time immemorial, especially during the very hot summer season. But the main reason why a new brand of sports drink made from coconut water was being developed is that coconut water contains naturally-occuring sugar and electrolytes-a fact that not many Filipinos are aware of. More specifically, it is relatively high in potassium and low in soduim content, thus making it also a good substitute to hydrating-energizing drinks. CoCoBlast would come in two variants: CoCoBlast Isotonic and CoCoBlast Hypotonic- wherein the main difference between the two is that hypotonic variants sugar concentration is 31.15% lower than that of the isotonic variant. CoCoBlast Isotonic would be for sports that cause excessive sweating and at the same time require the immediate boost of energy while performing the physical activity. CoCoBlast Hypotonic, on the other hand, would be beneficial for activities that result in fluid loss but does not require the immediate energy-boost during the sports performance. CoCoBlast would only contain the naturally-occuring electrolytes inn coconut water, thus making it healthier and more natural. Detailed research and analysis proved that the electrolyte-content of coconut water suffice, even exceeds, the required amounts in sports drinks. Also, only a minimal amount of artificial sugars would be added in the formulation. These sugars would come in the form of sucrose and glucose monohydrate. Lastly, each bottle of yhe sports drink would contain 80% coconut water solution, while the remaining 20% would include processed water, various forms of preservatives and flavor enhancers, and other dry components (namely protein and B- complex vitamins) that would enhance the body's carbohydrate-utilization and the athletes mental alertness during sports performance. CoCoBlast's target market will consist of 15-to-39-year old individuals, of both gender, residing in the National Capital Region with an annual family income of atleast Php210.000 and who are playing sports either on a regular basis or for leisure only. To test the market feasibility of CoCoBlast, a survey was conducted on individuals belonging to the target market specified above. Result showed that about 34% of the target market consider themselves as "into sports" or physical Activities, and, out of the, 62.75% are willing to buy a sports drink made from coconut water. Using the facts, it was show that CoCoBlast can capture a market share of at least 21%. Furthermore, through intensive marketing strategies, the demand for CoCoBlast was projected to increase from 377,954 liters in 2011 to 2,045,548 liters in 2015. This is approximately equivalent to a market share of 5% in 2011 and up to 25% in 2015. To support these demand and market share projections, appropriate marketing strategies should be put in place. These would include the traditional forms namely: print advertising, in sports oriented shows, and later on in primetime TV; flyers, brochures, and posters; and intensive product sampling especially during the launching year. New marketing strategies shall also be implemented, namely: fun run (marathon) and dance competition sponsorships in order to create more buzz about the product; and the implementation of virtual CoCoBlast kiosks in canteens and cafeteria lacated in gyms, fitness centers, and other strategic locations. In terms of technical feasibility, the main issue on lengthening the shelf life of the product since it is a fact that coconut water is easily contaminated and that its general life-span using simple preservative processes is only one week. indeed, several preservatives such as sodium benzoate and sodium citrate dihydrate are available. However, the keeping quality would not be secured unless an accurate process is properly defined. Through intensive research, and with some assistance from the Philippine Coconut Authority, a production process for CoCoBlast was developed. It includes a combination of both manual and mechanical process geared towards lengthening the products shelf life. The most important operations are the filtration, pasteurization, mixing, oil removal, repasteurization, and final mixing operations. The involvement of several mechanical processes in production entails the need to purchase a number of machines. The most important machine, aside from the mixers, filters, and centrifuges, is the high temperature-short time (HTST) heating unit which is used in the pasteurization process. The said machine will be very vital in removing spoilage-causing micro organisms and ultimately increase the products shelf life. Using the defined production process for CoCoBlast, its life span was increased to somewhere in between 9 months to a year. Since CoCoBlast would be manufactured in large amounts, a site that would house the production plant also had to be located. The most important consideration in this case was to find a site that would be closest to the supplier of the most delicate and the most vital ingredient-that is a site closest to the source of coconut water. The largest suppliers of coconut are located in Cavite, Laguna and Quezon. However, Laguna was closest to Metro Manila, the targeted geographic location of CoCoBlast. After careful selection, it was decided that purchasing a warehouse for sale in Sto. Tomas, Biñan, Laguna would be most beneficial for manufacture of CoCoBlast. Upon production, the finished goods must be stored somewwhere, prior to dispatch to large supermarkets, grocery stores, and other distribution channels. Thus, a finished goods warehouse also have to be located. This warehouse must be located closed enough to the customers in order to reduce product damage during delivery. Such a requirement implied that the finished goods warehouse should be within Metro Manila. After careful selection, a small warehouse in Makati was chosen as the storage area for CoCoBlast sports drinks. CoCoBlast manufacture would involve the production of thousands, even millions of bottles of sports drinks. It would also require the establishment of a production plant and a complex distribution system. Ultimately, such an arrangement would involve a lot of stakeholders involved with manufacture, distribution, and sales of CoCoBlast. Thus, CoCoBlasts ownership would be in form of a corporation. Considering all potential cost involved, the total project cost was calculated to be about Php 38,019,603.78. Twenty-Five (25%) percent of this amount would be aquired to loans from lending institutions. The remaining 75% would come from the issuance of common stocks to investors. Through intensive financial analysis, it was established that the company owning CoCoBlast would become stable through the years. This means that over time, CoCoBlast would be able to offer greater protection to its creditors, the firm would be able to meet its long-term obligations, and the value of the capital invested by the owners is continually increasing over time. Using the net present value principle, it ws shown that the NPV is Php 8,400,453.11. Since the NPV is positive sign of profitability is the fact that the computed payback period is four years-which means that at the end of 2014, all initial investments would be repaid and all succeeding cash in flows would proceed to the companys profits. With the establishment of a significant amount of potential market share, through the support of intensive and aggressive marketing strategies, it was established that the CoCoBlast project is market feasible. Since there are available materials, machines, processes, and technology for producing CoCoBlast, it was also established that the CoCoBlast project is technically feasible. Positive financial projections also proved that the CoCoBlast project is financially feasible. Taking these as a whole, it can be Concluded that the CoCoBlast project is indeed feasible.